What Future for the Pandemic Treaty? The Chinese Contribution to the Implementation and Evolution of the Health Security Regime (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
Following the Seventy-Seventh World Health Assembly last May, the member states of the World Health Organization (WHO) have decided to give themselves an additional twelve months to work on the content of the long-awaited Pandemic Treaty, with hopes kept alive by the successful revision of the International Health Regulations (IHR). The latter was an encouraging outcome considering the tensions among different regional groups that arose during both negotiation processes, initiated in the Covid-aftermath to strengthen the existing Health security regime.Despite the increasing attention to China’s participation in international institutions, the country’s involvement in the global Health Security Regime has been neglected, at least until recently. This article will consider the transformation of the Health Security Regime (HSR) from its inception to the present day, focusing on Beijing’s compliance with the Regime, delving into the government’s changed approach to managing epidemic and pandemic crises, and finally reviewing the main claims raised by the Chinese delegation during the negotiations for the drafting of the New Pandemic Treaty.
Keywords: New Pandemic Treaty; Health Security; China; World Health Organisation; Health Diplomacy